"There's no reason he needs to come in on that": Defining territory marking by watching Australia's Bachelor in Paradise. Issue 2 (17th February 2022) - Vogels, Christina
ABSTRACT: This article examines the gendered nature of territory marking. Territory marking, for this discussion, refers to the practice that entitles men to claim ownership over a woman who they are involved with romantically by threatening other men who appear to be 'making moves on' or flirting with her. Despite it being a recognised practice in society, feminist scholarship—and more broadly, sociological research—on territory marking is scarce. This gap in scholarship is concerning as the practice itself speaks to engrained gendered dynamics that enable men to oppress women by not only controlling who they can interact with but also by objectifying them as objects to be fought over. It is therefore important to find opportunities when this practice materialises, in order to document not only what it looks like but also to interrogate the gendered rules that surround it. This article does this work by using depictions of territory marking within Australia's Bachelor in Paradise to offer new definitions of how this practice takes form and develops. While this analysis does not claim to provide a definitive account of territory marking, it offers scholarship a deeper understanding of the gendered elements that can make up this practice.